Angiogenesis as a diagnostic factor in primary breast cancer: microvessel quantitation by stereological methods and correlation with color Doppler sonography - Grischke, Eva-Maria; Kaufmann, Manfred; Eberlein-Gonska, Maria; Mattfeldt, Torsten; Sohn, Christof; Bastert, Gunther (Onkologie, 1994)
Background: In contrast to benign lesions without signs of inflammation, malignant tumors have a capacity for angiogenesis. Therefore it was of interest to evaluate with color Doppler ultrasound if breast carcinomas showed higher vascularization than benign lesions. To enable a correlation with the pathoanatomic situation of vascularization, stereological methods were used to quantify microvessel volume, surface and length as indicators for angiogenesis. Patients and Methods: Two hundred and five patients with a palpable and/or mammographically seen breast tumor were investigated before they underwent surgery with color Doppler ultrasound for the detection of blood flow in the tumor or in an area around the tumor within a distance of 2 cm. In 101 cases microvessels of the tumor were identified by immunohistochemistry using the monoclonal mouse antibody (JC70) that detects the vascular endothelium-associated antigen CD31 and quantified by stereological methods. The quantified vessel volume, surface, and length were compared to color flow results and other prognostic factors in breast cancer. Results: The detection of blood flow by color Doppler sonography in the tumor and in the peritumoral region was significantly higher in malignant than in benign breast lesions (p = 0.003). By stereological quantitation of microvessels it could be shown that breast carcinoma had a significantly higher volume, surface and length of vessels than fibroadenoma (p < 0.00001 and p < 0.0001). In the group of breast cancers a significant correlation was found between high length of microvessels per mm3 tumor and tumor size (p = 0.04 - Jonckheere test), a negative estrogen receptor (p < .007) and a negative progesterone receptor (p = 0.005). No correlation was found between microvessel length and nodal status, tumor grade, ploidy status, and S-phase fraction. Conclusions: Microvessel count in breast tumors, using the JC70 antibody to CD31, and stereology for quantitation in a three-dimensional fashion, is an effective method to look for the extent of angiogenesis and to correlate Doppler flow results with pathoanatomic vascular data. With color Doppler sonography an effective clinical method is available for distinguishing between benign and malignant lesions.